Sustainable paper from agricultural residues: differentiating treatment effects in banana pseudostem fibers using X-STATIS multiblock analysis - Romero-Cárdenas, Erika; Romero-Romero, Byron Ramiro; Tapia-Núñez, Diego Wladimir; Zúñiga-Santillán, Xiomara Leticia; Valenzuela-Cobos, Juan Diego (Frontiers in Sustainability, 2025)
IntroductionThe sustainable valorization of agricultural waste is key to advancing circular economy models and reducing environmental impacts. Banana pseudostem (Musa spp.), an abundant byproduct of tropical agriculture, is evaluated as a renewable raw material for eco-friendly papermaking.MethodsFour treatments were applied to banana pseudostem pulp: untreated, naturally fermented, starchenhanced, and mechanically re-homogenized. Key physical and mechanical properties basis weight, caliper, and tear resistance were measured. Data were analyzed using Partial Triadic Analysis (X-STATIS) to assess structural differences and consistency.ResultsNatural fermentation improved fiber bonding, starch addition significantly increased mechanical strength, and mechanical re-homogenization negatively affected structural integrity. Distinct differences in paper quality were observed among treatments.DiscussionBanana pseudostem shows strong potential as a sustainable lignocellulosic resource for papermaking. Optimized treatments improve material properties, supporting agro-industrial waste valorization and contributing to circular bioeconomy practices in tropical regions.